(untitled) (De Musica, 2023)
The article aims to reflect - in a dialogic form with interludes - on some issues concerning musical interpretation and performance in Luigi Pareyson’s work, in an admittedly partial reconnaissance of the philosopher’s articulated research path in its fundamental phases: an aesthetics accomplished as a theory of formativity, a hermeneutics developed as an ontology of the inexhaustible, a theocentric ontology of freedom.